18‐2: Invited Paper: Liquid Crystal Lenses in Augmented Reality. Issue 1 (2nd June 2017) - Lin, Yi-Hsin; Wang, Yu-Jen
Abstract : Electrically tunable lens power of liquid crystal (LC) lenses attracts many applications. The basic mechanism, structures, and development of LC lenses are reviewed. How LC lenses assist in registration of images and vision correction in augmented reality is discussed.